2021
DOI: 10.1159/000519198
|View full text |Cite
|
Sign up to set email alerts
|

Successful Surgical Intervention of Strangulated Ileus with a Simple Cut of the External Iliac Vein without Vein Reconstruction

Abstract: A 67-year-old woman with epigastralgia was referred to our hospital. The patient had undergone hysterectomy, bilateral oophorectomy, omentectomy, and radical pelvic and para-aortic lymph node dissection for her ovarian cancer 6 years before. Despite the gastrointestinal decompression therapy under the presumed diagnosis of adhesive ileus, computed tomography scans taken 3 days after the onset of epigastralgia showed marked dilatation of the small intestine and an oval high-density mass, that is, thrombi, in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…It is particularly interesting that about half of reports have originated from the gynecologic field, in which all the initial gynecologic surgeries were done laparoscopically [ 13 , 17 23 ]; moreover, approximately one-third of those reports were from the urologic area, in which the primary operations, except for the first case reported, were laparoscopic or robot-assisted surgeries [ 12 , 24 28 ]. Recently, two reports described three cases after rectal cancer surgeries [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is particularly interesting that about half of reports have originated from the gynecologic field, in which all the initial gynecologic surgeries were done laparoscopically [ 13 , 17 23 ]; moreover, approximately one-third of those reports were from the urologic area, in which the primary operations, except for the first case reported, were laparoscopic or robot-assisted surgeries [ 12 , 24 28 ]. Recently, two reports described three cases after rectal cancer surgeries [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to past papers, vessels or nerves constructing the internal hernia orifice were right common iliac artery (3 cases) [ 12 , 18 , 24 ], left external iliac artery and/or vein (4 cases) [ 17 , 22 , 25 , 27 ], right external iliac artery and/or vein (4 cases) [ 13 , 20 , 23 , 26 ], right superior vesical artery (3 cases) [ 21 , 29 ] and right umbilical artery and/or obturator nerve (5 cases) [ 19 , 28 , 30 ]. In fact, PL-related SBO is more common on the right side than on the left side (Table 1 ), which might be attributable to the fact that the left side is covered with the sigmoid colon.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On reduction of ischemic small bowel hernia, Dumont and Wexels [ 10 ] and Zhang et al [ 19 ] found the small bowel to be viable after warming it, so a resection was not done. Similarly, Hishikawa et al [ 18 ] and Chaconas et al [ 23 ] did not have to resect the small bowel as it was not ischemic. The mean hospital length of stay was 12.7 days for the 13 articles that reported it.…”
Section: Reviewmentioning
confidence: 99%
“…Chowdary and Wright [ 20 ] left the defect open due to concerns regarding bacterial contamination of the closing material. Hishikawa et al [ 18 ] chose not to close the defect because it divided the external iliac vein itself, underneath which the bowel was herniating. The second most common approach was to close the hernia defect with peritoneal flaps [ 6 , 12 , 21 ] and suture close [ 17 , 19 , 23 ].…”
Section: Reviewmentioning
confidence: 99%